A Guide to Study Iron Oxide Magnetic Nanoparticles with Biomedical Applications. Part II (2017)
In this second part, the magnetic nanoparticles characterization is studied, doing special emphasys in the properties interpretation in order to define the nanosystems applications. In the case of the iron oxide magnetic nanoparticles, the influence of its properties in the heat dissipation under radiofrequency fields is analyzed, this answer is usefull in the cancer treatment by magnetic hyperthermia. In the magnetic hyperthermia treatment, particles absorb energy from a radio frequency magnetic field and dissipate it as heat. For in-vivo test and human assays, frequency ranges between 50 and 1000 kHz and field amplitudes ranges between 5 and 150 kHz are usually used. The main properties, such as magnetization, interactions between particles and particles structuring are studied using experimental data, computational simulations and suitable models for each case studied in the part I of this article. Finally, a correlation between these properties with heat dissipation, measured by calorimetric methods, which is the merit parameter to quantify the electromagnetic energy transduction into heat, is pointed out.